2008
DOI: 10.1007/s00423-008-0413-4
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive video-assisted subtotal parathyroidectomy with thymectomy for secondary hyperparathyroidism

Abstract: Minimally invasive video-assisted subtotal parathyroidectomy offers an alternative method, and this technique can be performed safely for sHPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
1
6
1
1
Order By: Relevance
“…We defined the conversion rate and number of removed parathyroid glands as parameters of feasibility. The conversion rate of 9.4% in this study is noticeably lower than that reported in previous studies of MIVAP for rHPT (0–30%) and therefore is acceptable [ 21 , 25 ]. We suggest that the conversion rate would decrease with increasing experience in MIVAP.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…We defined the conversion rate and number of removed parathyroid glands as parameters of feasibility. The conversion rate of 9.4% in this study is noticeably lower than that reported in previous studies of MIVAP for rHPT (0–30%) and therefore is acceptable [ 21 , 25 ]. We suggest that the conversion rate would decrease with increasing experience in MIVAP.…”
Section: Discussioncontrasting
confidence: 65%
“…We suggest that the conversion rate would decrease with increasing experience in MIVAP. The number of removed parathyroid glands in the MIVAP group did not differ from that in the conventional surgery study, confirming the feasibility of MIVAP for rHPT [ 21 , 25 ]. The number of approximately 3.5 in both groups corresponds to subtotal parathyroidectomy with transcervical thymus resection the best surgical strategy for patients currently listed for kidney transplantation [ 7 , 31 ].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…PTX is performed as either subtotal PTX, where the aim is to keep parathyroid tissue corresponding to one normal gland, and total parathyroidectomy, aiming at removing all parathyroid tissue. Parathyroidectomy is usually performed with open surgery through a Kocher cervical incision in general anesthesia (Lorenz et al 2015), although there have been reports on minimally invasive PTX (Barbaros et al 2009, Sun et al 2009, Alesina et al 2010. Subtotal and total PTX can both be combined with transcervical thymus resection and/or parathyroid autotransplantation.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Die Schnellschnitthistologie hat ihren Wert in der bedarfsweisen Bestätigung der Exstirpation von hyperplastischem Nebenschilddrüsengewebe und wird daher als fakultative Maßnahme bei Operationen wegen eines renalen Hyperparathyreoidismus eingeordnet. Minimalinvasive, voll endoskopische und videoassistierte Verfahren zur chirurgischen Therapie des sHPT sind als erfolgreich durchführbar beschrieben worden, haben bisher jedoch nur wenig Anwendung gefunden [38][39][40].…”
Section: üBersicht E48unclassified